Properties of STAT1 and IRF1 enhancers and the influence of SNPs - Abou El Hassan, Mohamed; Huang, Katherine; Eswara, Manoja B K; Xu, Zhaodong; Yu, Tao; Aubry, Arthur; Ni, Zuyao; Livne-bar, Izzy; Sangwan, Monika; Ahmad, Mohamad; Bremner, Rod (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background STAT1 and IRF1 collaborate to induce interferon-γ (IFNγ) stimulated genes (ISGs), but the extent to which they act alone or together is unclear. The effect of single nucleotide polymorphisms (SNPs) on in vivo binding is also largely unknown. Results We show that IRF1 binds at proximal or distant ISG sites twice as often as STAT1, increasing to sixfold at the MHC class I locus. STAT1 almost always bound with IRF1, while most IRF1 binding events were isolated. Dual binding sites at remote or proximal enhancers distinguished ISGs that were responsive to IFNγ versus cell-specific resistant ISGs, which showed fewer and mainly single binding events. Surprisingly, inducibility in one cell type predicted ISG-responsiveness in other cells. Several dbSNPs overlapped with STAT1 and IRF1 binding motifs, and we developed methodology to rapidly assess their effects. We show that in silico prediction of SNP effects accurately reflects altered binding both in vitro and in vivo. Conclusions These data reveal broad cooperation between STAT1 and IRF1, explain cell type specific differences in ISG-responsiveness, and identify genetic variants that may participate in the pathogenesis of immune disorders.